1996
DOI: 10.1074/jbc.271.31.18535
|View full text |Cite
|
Sign up to set email alerts
|

Domains of DnaA Protein Involved in Interaction with DnaB Protein, and in Unwinding the Escherichia coli Chromosomal Origin

Abstract: DnaA protein of Escherichia coli is a sequence-specific DNA-binding protein required for the initiation of DNA replication from the chromosomal origin, oriC. It is also required for replication of several plasmids including pSC101, F, P-1, and R6K. A collection of monoclonal antibodies to DnaA protein has been produced and the primary epitopes recognized by them have been determined. These antibodies have also been examined for the ability to inhibit activities of DNA binding, ATP binding, unwinding of oriC, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
134
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(139 citation statements)
references
References 44 publications
4
134
1
Order By: Relevance
“…Prepriming Complex Formation-Plasmid DNAs and purified proteins have been described previously (10,14). To separate the steps of assembly of the prepriming complex from downstream events of priming and DNA replication, staged incubations were performed (15).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prepriming Complex Formation-Plasmid DNAs and purified proteins have been described previously (10,14). To separate the steps of assembly of the prepriming complex from downstream events of priming and DNA replication, staged incubations were performed (15).…”
Section: Methodsmentioning
confidence: 99%
“…The highly negatively supercoiled DNA termed F1* is the product of this assay. Finally, prepriming complex formation can be shown by the specific retention of DnaA and DnaB (and also DnaC if the prepriming complex is formed with ATP␥S instead of ATP) at oriC by immunoblot analysis of isolated complexes (10) or by electron microscopy (9,19).…”
Section: Conditions Optimal For Preprimingmentioning
confidence: 99%
“…Specific interaction between DnaA and the DnaB helicase (9,10) recruits the helicase and contributes to its loading by a helicase loader, the DnaC protein (11). Interactions between DnaB and the τ-subunit of polymerase (12), as well as DnaB and primase (13), contribute to replisome assembly at Escherichia coli oriC.…”
mentioning
confidence: 99%
“…The DnaA complex unwinds and opens several AT-rich segments of doublestranded DNA within the origin and stabilizes the resulting single-strands. DnaA then recruits the DnaB helicase with help from DnaC to form the "prepriming complex" [1]. After priming of the singlestranded DNA, replication occurs by the action of DNA Polymerase III.…”
mentioning
confidence: 99%
“…In addition to oligomerization, cross-linking studies have shown that the N-terminal domain of DnaA interacts directly with both DnaB [1] and the regulatory protein DiaA [21]. For DnaB, the regions of interaction were further defined by solid phase binding assays, which showed that residues 24-86 from the N-terminal domain, as well as residues in domain III, were important [20].…”
mentioning
confidence: 99%